2021
DOI: 10.3390/ijerph18084243
|View full text |Cite
|
Sign up to set email alerts
|

Narcissism and Exercise Addiction: The Mediating Roles of Exercise-Related Motives

Abstract: The present research examined whether the associations that narcissistic personality features had with exercise addiction were mediated by particular motives for engaging in exercise in a large Israeli community sample (N = 2629). The results revealed that each aspect of narcissism was positively associated with exercise addiction. Narcissistic admiration and narcissistic rivalry had similar positive indirect associations with exercise addiction through the interpersonal motive for exercise. However, these asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…Furthermore, populations investigated are comparable to ours, while both studies were also conducted on fitness center users. Zeigler-Hill et al investigated the relationship between narcissism and exercise addiction through motives of fitness users and they found complex correlations with different aspects of narcissism and different motives, such as body image and narcissistic admiration [ 19 ]. This study was conducted on general population, and two scales were used for measurement of narcissism: Narcissistic Admiration and Rivalry Questionnaire and Narcissistic Vulnerability Scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, populations investigated are comparable to ours, while both studies were also conducted on fitness center users. Zeigler-Hill et al investigated the relationship between narcissism and exercise addiction through motives of fitness users and they found complex correlations with different aspects of narcissism and different motives, such as body image and narcissistic admiration [ 19 ]. This study was conducted on general population, and two scales were used for measurement of narcissism: Narcissistic Admiration and Rivalry Questionnaire and Narcissistic Vulnerability Scale.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, reasons for exercise can go beyond just a simple idea of a health. Recently, some studies have found a link between extensive exercise and the narcissistic personality through motives such as body image, rivalry and pathologically needed admiration [ 19 ]. One of the well-established components of narcissism is the tendency to addictive behaviors, which can among others present through exercise addiction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with substance use disorders or dependence have mostly high neuroticism and low openness and/or agreeableness [49]. Some studies have explored the association between personality traits and ED [52][53][54]. In 2017, Bircher et al conducted a systematic review with conflicting results and concluded that if personality factors were involved in exercise addiction, the current knowledge is insufficient to draw a specific profile of the personality of a person with exercise addiction, and further studies with more representative samples are needed [55].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the relationship between narcissism and ED [ 33 , 34 ] have suggested that narcissism may predict FA. This relationship may be rooted in low self-esteem and negative ideas about one’s self [ 35 ]. Low self-efficacy may be another psychological variable predisposing individuals to symptoms of FA [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%